FRI0430 Golimumab in Refractory Uveitis Related To Spondyloarthritis. Multicenter Study of 15 Patients. (15th July 2016) - Palmou-Fontana, N.; Calvo-Río, V.; Blanco, R.; Santos-Gomez, M.; Rubio-Romero, E.; Cordero-Coma, M.; Gallego-Flores, A.; Verόz, R.; Torre, I.; Hernández, F.F.; Atanes, A.; Loricera, J.; et al.
Abstract : Objectives: To assess the efficacy of golimumab (GLM) in refractory uveitis associated to spondyloarthritis (SpA). Methods: Multicenter study of SpA-related uveitis refractory to at least one immunosuppressive drug. The main outcome variables were degree of anterior and posterior chamber inflammation, visual acuity, and macular thickness. Results: Fifteen patients (13 men/2 women; 18 affected eyes; mean age 39±6 years) were evaluated. The underlying SpA subtypes were ankylosing spondylitis (n=8), psoriatic arthritis (n=6) and non-radiographic axial SpA (n=1). The ocular involvement patterns were recurrent anterior uveitis in 8 patients and chronic anterior uveitis in 7. Before GLM they have received methotrexate (n=13), sulfasalazine (n=6), pulses of methylprednisolone (n=4), azathioprine (n=3), leflunomide (n=2) and cyclosporine (n=1). Ten of them had also been treated with TNF-α blockers; etanercept (n=7), adalimumab (n=7), infliximab (n=6), and certolizumab (n=1). GLM was given at the standard dose (50 mg/sc/monthly) as monotherapy (n=7) or in combination with conventional immunosuppressive drugs (n=8), mainly methotrexate. Most patients had rapid and progressive improvement of intraocular inflammation parameters. The median number of cells in the anterior chamber at 2 years (0 [0–0]) was significantly reduced compared to baseline findings (1 [0–3]); p=0.04). The mean best corrected visual acuity value also improved (0.84±0.3 at 2 years versus 0.62±0.3 at baseline; p=0.03). Only minor side effects were observed after a mean follow-up of 23±7 months. Conclusions: Our results indicate that GLM may be a useful therapeutic option in refractory SpA-related uveitis. Disclosure of Interest: None declared